Desenvolvimento de dispositivos analíticos baseados em papel usando materiais de custo baixo - Pradela Filho, Lauro Antonio (2020)
Analytical devices fabricated on paper were developed in this work. Paper-based electrodes (PEs) were prepared using conductive inks based on carbon powder and colorless nail polish or glass varnish, which were used as alternative and low-cost binders. Office paper and quantitative filter paper were used as substrates on which the conductive inks were applied. The fabrication of the PEs was reproducible (RSD < 10%, n = 4 for Ip obtained for [Fe(CN)6]4-), and the electrodes were used for dopamine determination using differential pulse voltammetry. For PEs/nail-polish, the linear range was 30 to 100 μmol L-1 and the limit of detection (LD) was 5.2 μmol L-1. For EPs/Glass-varnish, the linear range was 15 to 100 μmol L-1 and the LD was 4.1 μmol L-1. The potentiality of the EPs/Glass-varnish was also evaluated for catechol and hydroquinone using linear sweep voltammetry. The linear range for both species was 10 to 100 μmol L-1 with LD of 9.0 μmol L-1 for catechol and 5.3 μmol L-1 for hydroquinone. Therefore, the results showed that PEs provided satisfactory results for phenolic compounds, opening possibilities for new applications. Paper-based microfluidic systems coupled with thermoplastic electrodes (TPEs) were also developed in this work. TPEs were fabricated by mixing 1: 1 (w:w) carbon black and polycaprolactone. The microfluidic devices were produced with two reservoirs, which were responsible for producing a rapid and continuous flow driven by gravity and capillarity. The proposed device does not require external pumps as propulsion units, ensuring better portability. The performance of these devices was improved by increasing the wicking capacity of the system, which significantly increased the number of injections possible with a single device. The injection volume is relatively low (2 μL). In addition, the microfluidic system showed satisfactory parameters such as repeatability of injection (RSD = 2%, n = 6 for Ip obtained for FcTMA+) and reproducibility of fabrication (RSD = 10%, n = 3 for Ip obtained for FcTMA+). The applicability of the microfluidic device was separately evaluated for the quantification of caffeic acid and tryptamine in food and drinks and the results showed reliability and viability. Therefore, this work shows some inexpensive strategies to produce disposable electrodes and microfluidic devices, bringing some possibilities for new analytical applications.